Digital Learning Across Boundaries: Immersive technologies supporting changemaking in an international context - Emma Whewell; Helen Caldwell; Beth Garrett; Grant Malloch (Research in Education and Learning Innovation Archives)
The Digital Learning Across Boundaries: Developing Changemakers (DLAB) project uses immersive technologies in education to explore three challenges across three years: physical, personal and environmental. This paper focuses on the first of these, bringing together the themes of digital making and changemaking to cross physical boundaries by raising awareness about physical inactivity in 11 and 12 year old school pupils. Immersive technologies such as augmented and virtual reality enabled the development of empathy and intercultural understanding among participants, fostered an understanding of changemaking, and created environments for sharing prototype exergames. Research data is analysed to seek evidence of the development of changemaker attributes and impact within a sample group of 60 English school pupils.